2022
DOI: 10.3390/jpm12091355
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 3D Modeling Workflows Using Dental CBCT Data for Periodontal Regenerative Treatment

Abstract: The cone beam computed tomography (CBCT) technology is nowadays widely used in the field of dentistry and its use in the treatment of periodontal diseases has already been tackled in the international literature. At the same time, advanced segmentation methods have been introduced in state-of-the-art medical imaging software and well-established automated techniques for 3D mesh cleaning are available in 3D model editing software. However, except for the application of simple thresholding approaches for the pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…The necessity for re nements in the automated segmentation is also reported in the study by Verykokou et al [22], who tested different methods for alveolar bone segmentation, with the aim of designing and producing 3D scaffolds for periodontal regeneration. The author found that the fully automated method was not able to produce satisfactory results for the purpose of producing 3D models of the hard tissues.…”
Section: Discussionmentioning
confidence: 74%
“…The necessity for re nements in the automated segmentation is also reported in the study by Verykokou et al [22], who tested different methods for alveolar bone segmentation, with the aim of designing and producing 3D scaffolds for periodontal regeneration. The author found that the fully automated method was not able to produce satisfactory results for the purpose of producing 3D models of the hard tissues.…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, they can be used for surgeon training purposes, through realistic simulation of surgical procedures [ 93 ]. Another widespread use of 3D modeling and 3D printing in medical and dental applications is the production of personalized implants adapted to the patient [ 94 ] and the production of 3D printed prosthetic limbs, as their 3D design, when it is personalized, is based on the 3D anatomy of the specific part of a patient’s body, acquired by medical scanners [ 94 , 95 , 96 , 97 ]. Efforts have also been made to 3D design artificial organs and tissues based on data from medical scanners [ 98 ].…”
Section: Applicationsmentioning
confidence: 99%
“…In our previous research [49], we evaluated segmentation and 3D modeling workflows using dental CBCT data by performing several comparisons between the 3D models of the hard tissues of the oral cavity of a patient with periodontitis, generated through different methodologies. This research led to the development of an optimal methodology that may be used for 3D modeling of the teeth and the alveolar bone of patients with periodontitis in the specific regions where the periodontal defects are observed.…”
Section: D Modeling Of Periodontal Defectsmentioning
confidence: 99%
“…The ultimate goal of this research is the creation of bioabsorbable 3D-printed scaffolds of personalized treatment against periodontitis, which will simultaneously be used as sustained-release drug carriers. In our previous work [49], we proposed an optimal methodology for 3D modeling of the alveolar bone and the teeth around periodontal defects using CBCT data, which was determined based on several experiments. In this article, we rely on our previous work by using and evaluating the proposed method for creating a 3D model of the teeth and the part of the alveolar bone where the periodontal defect is located.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation